2017
DOI: 10.37358/rc.17.7.5740
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease in Patients with Ankylosing Spondylitis: myth or reality?

Abstract: Although the relation between periodontitis (PD) and systemic disorders (e.g. cardiovascular diseases, diabetes and rheumatoid arthritis) is widely accepted, the association with ankylosing spondylitis (AS) is inconsistently mentioned. We prospectively examined the relationship between periodontal disease and AS, focusing on the rate and course of PD, factors associated with severity and the impact of anti-TNF-α treatment on inflammatory status. Standard assessments performed twice (week 0, week 24) included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In the non‐randomized clinical studies there is a general concordance that the anti‐TNF‐α therapy reduces alveolar bone loss and improves periodontal indices in patients who are not under periodontal treatment . However, two studies did not support these findings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the non‐randomized clinical studies there is a general concordance that the anti‐TNF‐α therapy reduces alveolar bone loss and improves periodontal indices in patients who are not under periodontal treatment . However, two studies did not support these findings.…”
Section: Resultsmentioning
confidence: 99%
“…Quality of information in non‐randomized clinical studies was considered high level in seven articles and moderate in the remaining studies . Quality of information in the In vivo animal studies was considered moderate in five articles and high in seven studies .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pivotal studies have already explored the role of different synthetic and biological therapies in active RA and comorbid periodontal disease, showing controversial results [ 5 , 9 , 12 , 16 , 17 , 25 , 28 , 35 , 36 , 37 , 38 , 39 ]. Overall, there is a trend to consider that TNF inhibitors, IL-6 receptor antagonist, B-cells depletive agents and, even, JAK inhibitors improve periodontal health in both RA and other arthritis (e.g., ankylosing spondylitis, psoriatic arthritis); it seems that all these drugs are ultimately effective in decreasing gingival and periodontal inflammation and, to a lesser extent, associated tissue damage [ 16 , 27 , 28 , 35 , 36 , 37 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Researchers even proposed a multistep approach of the sequential tissue repairing following TNF inhibitors, comprising reduced leukocytes traffic in the inflamed tissue, decreased proteolytic activity, and the normalization of osteoclast activity [ 1 , 5 , 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ancuta et al examined RA patients (n = 96) and Iordach et al examined AS patients (n = 86). Both studies showed a statistical significant decrease after 6 months of anti-TNF therapy in GI, BOP, PPD, and CAL (34,35). Since the literature has reported most frequently on the 6 months after treatment, the quantitative effects of before and after treatment on the 5 periodontal parameters is summarized in Figure 2.…”
Section: Days Anti-tnf May Improve Pi and Gimentioning
confidence: 94%